A 19th century whaler in Patagonia, Argentina: Dendrochronological analysis of the Bahía Galenses shipwreck - Mundo, Ignacio Alberto; Murray, Cristian; Grosso, Mónica; Rao, Mukund P.; Cook, Edward R.; Villalba, Ricardo
Since the late 18th century, the demand for products derived from the exploitation of cetaceans and pinnipeds led North American and European vessels to explore new hunting areas in the southern oceans. Numerous historical sources accounts for these commercial activities involving a great number of vessels. Many of these ships were lost at sea and their precise locations remain unknown. In 2002 the remains of a wooden shipwreck were discovered on the coast of Golfo Nuevo, northern Patagonia, Argentina. The wreck was named ?Bahía Galenses? after the historical name of the cove where it was found. The results of the archaeological research carried out so far indicate that it would be a whaler built in the 19th century employing northern hemisphere timbers. Some archaeological and written evidence suggest that it could be the Dolphin, a whaler built in Warren, Rhode Island, USA, in 1850 and shipwrecked in 1859 at Golfo Nuevo. To test this hypothesis, using dendroarchaeological provenance methods and a novel approach based on the gridded North American Drought Atlas (NADA), we found highly significant correlations between the wreck´s tree-ring width series and oak and pine chronologies from eastern US. Our findings indicate that the Bahía Galenses shipwreck have the same origin and historical moment of construction of the Dolphin. As far as we know, this research would the first study conducted in South America to date and determine the origin of a shipwrecked whaler through dendrochronological methods. The results of this study stimulate further interdisciplinary projects to study the large number of unidentified wooden shipwrecks found along the extensive Patagonian coasts of the South Atlantic Ocean, many of which may have been involved in the exploitation of marine resources during the 19th century. Fil: Mundo, Ignacio Alberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. ...